Magna Carta messed up the World, here’s how to fix it: the “logic” of capitalist development has left a nightmare of environmental destruction in its wake - Chomsky, Noam (Revista Hipótese, 2016)
This article is a translation by Ivan Fortunato, Ph.D., of “Magna Carta Messed Up the World, Here’s How to Fix It,”which first appeared in The Nation on March 23, 2015.